2021
DOI: 10.52547/jcmh.7.4.2
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Effectiveness of Cognitive Behavioral Therapy and Metacognitive Therapy on Depression, Suicide Ideation, and Masochistic Aggression in Individuals with Subclinical Symptoms of Body Dysmorphic Disorder

Abstract: Background and Purpose:The most common comorbid disorder with body dysmorphic disorder (BDD) is depression. Masochistic aggression and suicide are the main concerns about individuals with BDD who suffer from depression and have impaired function. Present study aimed to compare the effectiveness of cognitive behavioral therapy (CBT) and metacognitive therapy (MCT) on depression, suicide ideation, and masochistic aggression among individuals with subclinical symptoms of BDD. Method: This study was a quasi-experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The results showed that both CBT and ACT were effective in reducing high-risk behaviors in selfinjurious high school students. This finding is consistent with the prior results (Ahmadi & Valizadeh, 2021;As'hab et al, 2022;Babaee et al, 2022;Barnes et al, 2023;Entezari et al, 2021;Fitzsimmons-Craft et al, 2023;Hamidi et al, 2022;Jabraeili et al, 2014;Linehan, 1993;Nateghi & Sohrabi, 2017;Ofem, 2023;Rahimi et al, 2022;Rowland, 2010;Scheer et al, 2023;Spirito et al, 2011;Walser et al, 2015). Regarding this effectiveness, it can be said that ACT encourages clients to treat self-evaluations as mere thoughts and teaches individuals to correct negative self-assessments.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results showed that both CBT and ACT were effective in reducing high-risk behaviors in selfinjurious high school students. This finding is consistent with the prior results (Ahmadi & Valizadeh, 2021;As'hab et al, 2022;Babaee et al, 2022;Barnes et al, 2023;Entezari et al, 2021;Fitzsimmons-Craft et al, 2023;Hamidi et al, 2022;Jabraeili et al, 2014;Linehan, 1993;Nateghi & Sohrabi, 2017;Ofem, 2023;Rahimi et al, 2022;Rowland, 2010;Scheer et al, 2023;Spirito et al, 2011;Walser et al, 2015). Regarding this effectiveness, it can be said that ACT encourages clients to treat self-evaluations as mere thoughts and teaches individuals to correct negative self-assessments.…”
Section: Discussionsupporting
confidence: 89%
“…It also provided training on skills to control temptations and recognize tempting situations, understand their ability to control these situations, and remain hopeful for success, keeping them away from high-risk behaviors. Additionally, CBT has changed the self-perception of self-injurious students regarding their abilities and talents and the power E-ISSN: 2981-2526 they have to change matters, avoiding negative thoughts and suggestions, increasing their motivation to work and strive in various aspects of life, including education and work, and take firm steps towards achieving their goals with diligence and persistence (Entezari et al, 2021;Fitzsimmons-Craft et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subscales of this test have acceptable validity ranging from 0.68 to 0.92. No standardization of this tool was found in Iran; therefore, in this research, the psychometric findings of this tool were also examined indirectly (Entezari et al, 2021). The internal consistency results of this questionnaire in the current study were 0.86; moreover, the two-week retest reliability coefficient for a sample of 50 participants was 0.83.…”
Section: Body Self-imagementioning
confidence: 69%
“…Furthermore, individuals with eating disorders may engage in restrictive eating and compulsory exercise as a means to achieve an ideal body shape or weight, which can further perpetuate negative self-concept and body dissatisfaction (Simic et al, 2021). Effective treatment for eating disorders often involves addressing the negative selfconcept and body image issues, along with other psychological and behavioral factors (Entezari et al, 2021).…”
Section: Article Typementioning
confidence: 99%